1998
DOI: 10.1080/10790268.1998.11719506
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Care for Individuals with Spinal Cord Injury: Comparison of Four Approaches

Abstract: The efficacies of four bowel care regimens (bisacodyl suppositories, glycerin suppositories, mineral oil enemas and docusate sodium mini-enemas) were compared in seven subjects with traumatic spinal cord injury. Efficacy was assessed in terms of colonic transit time , bowel evacuation time and subjective responses to a questionnaire. Both docusate sodium mini-enemas and mineral oil enemas decreased total and left-sided colonic transit time. However, docusate sodium mini-enemas were superior to mineral oil enem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Bisacodyl (dulcolax) and glycerin are the most common active ingredients in these suppositories. Five studies (aggregate N ¼ 69) [19][20][21][22][23] examined the effect of suppositories on bowel management in SCI including one RCT and two controlled trials, which were not randomized ( Table 2). There is Level 1 evidence (from one good-quality RCT, however, with few subjects), 19 in addition to lower levels of evidence, [20][21][22] to support polyethylene glycol-based suppositories for bowel management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisacodyl (dulcolax) and glycerin are the most common active ingredients in these suppositories. Five studies (aggregate N ¼ 69) [19][20][21][22][23] examined the effect of suppositories on bowel management in SCI including one RCT and two controlled trials, which were not randomized ( Table 2). There is Level 1 evidence (from one good-quality RCT, however, with few subjects), 19 in addition to lower levels of evidence, [20][21][22] to support polyethylene glycol-based suppositories for bowel management.…”
Section: Resultsmentioning
confidence: 99%
“…The total bowel care time with the polyethylene glycol-based suppository is significantly less compared with hydrogenated vegetable oil-based bisacodyl suppositories. [21][22][23] Dietary fiber. There is Level 4 evidence (from one case series; N ¼ 11) 24 that high fiber diets may cause colonic transit time to increase, rather than decrease ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of interventional bowel-related studies in this population report very small samples and this may reflect generally low recruitment rates. 20 Among those that attended for the previous anorectal physiology study but who declined inclusion in this trial, a number of issues regarding BM research were identified. Many felt that they lacked time because of work, educational, family or carer commitments, BM had to fit into an often tight schedule.…”
Section: Discussionmentioning
confidence: 99%
“…There was an acceptance of the status quo; they had learned how to cope with their altered bowel function and BM as they now conducted it, possibly using reappraisal strategies. 20 Individuals indicated that allowing the research to impinge on their everyday life was unacceptable. These views underline how integral BM is to everyday life and illustrate why recruitment is so problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Use of suppositories has been shown to decrease duration of time spent on bowel care and the need for nursing/ caregiver assistance, specifically for PEG-based suppositories. 158,159,160,161,162 There is at least one good quality RCT study by House and Stiens that showed effective response to PEG-based bisacodyl suppositories for bowel management. 158 There are other studies with lower levels of evidence that support this finding.…”
Section: Glycerin Suppositorymentioning
confidence: 99%